Active / passive harmonic filters: Applications, challenges & trends - Motta, Lukas; Faundes, Nicolas (2016 17th International Conference on Harmonics and Quality of Power (ICHQP), 2016)
The goal of this paper is to present the different applications, challenges and trends for traditional active and passive harmonic filters for reduction of harmonic distortion and optimization of the power quality. Emphasis is put on real cases applied in the industry for passive tuned filters and for active harmonic filters analyzing the advantages and disadvantages of active versus passive filter technologies.